2022
DOI: 10.3390/w14111722
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Climate Variables and Geographical Distribution on Residential Drinking Water Demand in Ethiopia

Abstract: Water managers have increasingly shown that demand management solutions are more important than searching for alternative sources to resolve the challenges and shortages of water supply services. This study identifies the impact of climate variables on residential water demand in three geographically and spatially dispersed towns (Arba Minch, Ziway, and Debre Birhan) in Ethiopia. Monthly mean temperature, relative humidity, and precipitation are analyzed using multivariate regression models to identify and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This study serves as a continuation of two previous articles [15,25], conducted as part of the first author's PhD research. The findings and insights gained from these articles are integral to the current study.…”
Section: Datamentioning
confidence: 98%
See 3 more Smart Citations
“…This study serves as a continuation of two previous articles [15,25], conducted as part of the first author's PhD research. The findings and insights gained from these articles are integral to the current study.…”
Section: Datamentioning
confidence: 98%
“…According to Timotewos et, al. [25], the motivation for the study stems from the need to understand the factors contributing to the scarcity of water and the challenges faced by residents in urban areas of Ethiopia in accessing drinking water supply services. This understanding ensures better governance and helps to safeguard the long-term sustainability and access of Ethiopian people to drinkable water.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of rapid population and industrial growth, the demand for water by the domestic, commercial, and industrial sectors continues to rise while water availability continues to decline, further complicated by competing users, environmental degradation, and climate change [9]. A recent study by Timotewos MT et al [42] demonstrated that the impacts of topographical distribution and other anthropogenic activities on water demand are more significant than climate change in Arba Minch, Debre Birhan, and Ziway. The assessed water demand management measures from other nations, as shown in Table 1, mostly focus on educating the community to use less water.…”
Section: Future Potential Solutions Of Water Demand Management In Urb...mentioning
confidence: 99%